(untitled) (Fiep Bulletin - online, 2015)
In the past years the society has increased the search for the practice of physical activities aiming at the improvement in the quality of life, esthetic and the socialization among others objective. Since the Olympic Gymnastics is considered one of the oldest and most popular modality in sports of the Olympic program, and being the modality that generated more expectations in 2004 in Brazilian community due to the great variety of artistic movements, dynamic and static, of difficulty constituted by the coordination of extremely seductive plastic beauty. This activity shows in its base formation natural movements, gradually adaptable to the conditions of the athletes, what probably generates improvements in the motor coordination and the balance just by practicing it. The objective of this research was to identify if there was an improvement in the adaptive answers of motor coordination and the incurred balance on the practice of Olympic Gymnastics and the practice of the discipline of Physical Education in 7 years old girls of the City of Rio de Janeiro. A total of twenty-eight girls with the age of seven years old were evaluated, fourteen of the 28 were from the sports center, some were athletes of Olympic Gymnastics and the other fourteen from a City College, both located in the West Zone of the City of Rio de Janeiro. To evaluate the girls in question the reduced test of coordination of Bruininks-Oseretsky (1974) of motor proficiency was used, with the purpose to evaluate the performance of the motor abilities and the balance. Even though the girls from the Sports Center presented a bigger average on the tests of coordination than the girls from the College, these differences wasn’t significant statistically. This shows that the Olympic Gymnastics besides being an activity where there is the necessity of motor coordination and balance, the evaluated girls may not have had in an optimized way worked the psychomotor structures in their practices. Along with this information we could conclude that the activity of Olympic Gymnastics does not present differences in the adaptable answers of the motor coordination and the balance in girls of seven years old in this study. However there were variables that had not been controlled, as for example, the practices; the children leisure activities; the feeding; family habits and among others. This study recommends that more researches could be done about and more controlled variables so that it can be established a higher level of reliability.